High-risk and multiple human papillomavirus infections among married women in Can Tho, Viet Nam - Lan Thi Hoang Vu (Western Pacific Surveillance and Response, 2012)
Introduction: The two currently licensed human papillomavirus (HPV) vaccines are highly efficacious in preventing cervical pre-cancers related to HPV 6, 11, 16 and 18. Before implementing a large-scale HPV vaccine campaign in Viet Nam, information about the prevalence of infection with the HPV vaccine types is required. This study was done in Can Tho, the province with the highest prevalence of cervical cancer in the south of Viet Nam, to explore the distribution of other high-risk types of HPV among married women in this province.Method: The study employed a cross-sectional design with multistage sampling. A total of 1000 participants were randomly selected, interviewed and given gynaecological examinations. HPV infection status and HPV genotyping test were completed for all participants.Results: A broad spectrum of HPV types was reported in this study. The prevalence of cases infected with HPV 16 and/or 18 was 7%; the prevalence of cases infected with other high-risk HPV types was 6%. The highest prevalence for single and multiple infections, as well as for high-risk infections, was reported for the youngest age group (less than 30 years).Discussion: While it is relevant to implement an HPV vaccine campaign in Viet Nam due to the high prevalence of infection with HPV 16 and/or 18, it is important to note that one can be infected with multiple types of HPV. Vaccination does not protect against all types of high-risk HPV. Future vaccine campaigns should openly disclose this information to women receiving vaccines.